2022
DOI: 10.1029/2021jd035539
|View full text |Cite
|
Sign up to set email alerts
|

Future Characteristics of Extreme Precipitation Indicate the Dominance of Frequency Over Intensity: A Multi‐Model Assessment From CMIP6 Across India

Abstract: The intensification of the global hydrological cycle is the most consistent and ubiquitous signature of the changing scenario of climate in this 21st century's world (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 126 publications
3
14
0
Order By: Relevance
“…The estimated return level helps examine the extreme precipitation, leading to a derived Probable Maximum Flood (PMF), and it will be used to design high-risk infrastructures such as large dams and nuclear power plants where failure would be catastrophic (Visser et al, 2022). And this is consistent with previous findings that showed an increasing and shifting pattern of precipitation over the IRBs during the post-1980 (Chaubey et al, 2022;Sarkar & Maity, 2022). Also, this decline in rainfall over northeast India is consistent with previous researchers (Kuttippurath et al, 2021), which conclude that its due to the changes in land cover and become detrimental to vegetation activity.…”
Section: Changes In Extreme Precipitationsupporting
confidence: 84%
See 4 more Smart Citations
“…The estimated return level helps examine the extreme precipitation, leading to a derived Probable Maximum Flood (PMF), and it will be used to design high-risk infrastructures such as large dams and nuclear power plants where failure would be catastrophic (Visser et al, 2022). And this is consistent with previous findings that showed an increasing and shifting pattern of precipitation over the IRBs during the post-1980 (Chaubey et al, 2022;Sarkar & Maity, 2022). Also, this decline in rainfall over northeast India is consistent with previous researchers (Kuttippurath et al, 2021), which conclude that its due to the changes in land cover and become detrimental to vegetation activity.…”
Section: Changes In Extreme Precipitationsupporting
confidence: 84%
“…In this study, we used a multi-model approach to estimate the future changes in hydroclimate extremes over the IRBs. Many previous researchers have used the multi-model ensemble mean approach to finding the projected precipitation extremes and showed that this is the more robust analysis to estimate extreme events (Sarkar & Maity, 2022). To examine the changes in hydroclimate extremes over the IRBs, we divided the data sets into three-time frames from 2021 to 2040 for Near-future, 2041 to 2060 for Mid-future, and 2081 to 2100 for Far-future.…”
Section: Observed and Projected Data Setsmentioning
confidence: 99%
See 3 more Smart Citations